Influencia de los ejercicios neuromotrices para el mejoramiento de los procesos de atención en niños y niñas con discapacidad intelectual de la Escuela de Educación Especial 3 de Diciembre, del cantón Vinces, año 2023 - Carriel Fernández, Erick Stiven (2023)
Attention is considered as the cognitive capacity that the human being has to select, control and guide an action according to the focus of concentration that is had at a certain moment; However, children with intellectual disabilities are often very "distracted", and meaningful learning is little or not at all compared to a typically normal developing person; This is a consequence of the slowed maturation of neuronal processes that take place in the central nervous system. Objective of the research: To determine the influence of neuromotor exercises for the improvement of care processes in children with intellectual disabilities of the Special Education School "3 de Diciembre", Vinces Canton. Applied methodology: It had a mixed research approach, with a non-experimental – cross-sectional and exploratory – correlational design. A sample of 60 individuals: 12 teachers and 48 childrens with intellectual disabilities belonging to the Special Education School "3 de Diciembre", Vinces Canton, was selected. Instruments: The interview and the observation guide were used to evaluate the level of attention in the selected sample and to know the work methodology of the teachers in this situation. Results: There are attention problems in children with intellectual disabilities, as well as deficits in writing and communication. Teachers do not know about the types and application of neuromotor exercises in physical education class.